Clustering Analysis and Genome Inference of Pisang Raja Local Cultivars (Musa spp.) from Java Island by Random Amplified Polymorphic DNA (RAPD) Marker - Rasyadan Taufiq Probojati; Didik Wahyudi; Lia Hapsari (Journal of Tropical Biodiversity and Biotechnology, 2019)
Pisang Raja is an important local banana cultivar in the economy and cultural life in Indonesia, especially at Java. There are many Pisang Raja cultivars found on Java Island with various local names in each region, resulted in problems on taxonomic identification and grouping. Conventional research for grouping banana cultivars is still using morphological characters but considered inaccurate because of its subjectivity. This study aims to analyze the genetic diversity, grouping, and genome estimation of 13 local cultivars of Pisang Raja based on molecular approach using RAPD markers (OPA primers 1-20). Clustering and Principal Coordinates Analysis were performed to the amplified products using Paleontological Statistics (PAST) application version 3.15. Results showed that there were 12 primers which successfully amplified and produced DNA polymorphic bands in Pisang Raja, specifically OPA 1, OPA 2, OPA 3, OPA 4, OPA 5, OPA 8, OPA 16, OPA 17, OPA 18, OPA 19, and OPA 20. Pisang Raja cultivars considered have high genetic diversity, indicated by high polymorphic bands (95.17%) and low similarity coefficient values (0.2-0.6). Clustering and PCo analysis resulted in 3 clusters following its genomic group consist of AAA, AAB and ABB genomes, with Pisang Raja Bali as an outgroup (ABB). However, the separation of each cluster for genome inference was unclear. Cluster 1 consists of Pisang Raja Madu (AAB) and Raja Sereh (AAB). Cluster 2 consists of AAA and AAB genomes; includes Pisang Raja Jambe (AAA), Raja Kriyak (AAA), Raja Kutuk (AAB), Raja Brentel (AAB), Raja Seribu (AAB), and Raja Lini (AAB). Cluster 3 consists of AAA and AAB genomes, includes Pisang Raja Kisto (AAA), Raja Delima (AAA), Raja Bandung (AAB) and Raja Gareng (AAB). While Pisang Monyet (AAw) and Klutuk Wulung (BBw) as wild relatives were nested in Cluster 2. There were some different results of genome estimation based on RAPD markers compared to morphological characterization, and other molecular techniques. The use of RAPD markers is quite efficient and effective for studying genetic diversity and identifying genomes in bananas.